Sense of community through supportive housing among formerly homeless individuals with serious mental illness. Issue 1 (2nd January 2017) - Forenza, Brad; Lardier, David T.
ABSTRACT: Much research documents the correlation between homelessness and mental illness. Often, existing research focuses on deficits that live at the intersection of these phenomena. The present study utilizes a sense of community (SOC) framework to interrogate the ways in which formerly homeless individuals with serious mental illness perceive and experience community in supportive housing. Through focus groups with 18 consumers, this study contextualizes dimensions of SOC (membership, emotional connection, needs fulfillment, and influence) for the aforementioned population. Analysis of focus group data produced 16 themes and subthemes that support and extend our understanding of SOC for a population often conceptualized as isolated and alone. Implications for policy and practice emphasize: (1) the importance of supportive housing communities and the call for policymakers to increase funding for such programing; and, (2) that practitioners facilitate housing members' voices to effectuate change in supportive housing and increase SOC.